Communication Gaps and Integration: A Study of the Theory of Culturally Accommodating Communication in Korean Automotive Companies in Jakarta - Ade Mahendra (Eduvest - Journal of Universal Studies, 2026)
The expansion of Korean automotive companies into Indonesia has created an intensive environment for cross-cultural communication between Korean expatriates and Indonesian employees. This study addressed the urgency of understanding communication dilemmas arising from hierarchical organizational structures and differing cultural expectations. Using Communication Accommodation Theory (CAT) as the theoretical framework, this research explored how communication strategies, including convergence, divergence, maintenance, and overaccommodation, shaped daily workplace interactions. A qualitative case study approach was employed, involving purposive sampling of Korean expatriates and Indonesian employees. Data were collected through semi-structured interviews, participatory observations, and company document analysis. Thematic analysis revealed that convergence fostered relational solidarity but also placed psychological burdens on local employees; divergence reinforced authority but reduced employee participation; maintenance supported operational efficiency but created perceptions of indifference; and overaccommodation reduced motivation by being perceived as patronizing. These findings highlight that organizational effectiveness is not determined solely by structural efficiency but also by the quality of balanced intercultural communication. The novelty of this study lies in integrating Communication Accommodation Theory (CAT) with the paradoxes of communication within hierarchical multicultural organizations, providing theoretical contributions to cross-cultural communication studies and practical implications for developing inclusive leadership approaches and intercultural training programs. Future research may extend this framework to other multinational sectors to further examine the adaptability of CAT across diverse cultural contexts.